La participación de los receptores Toll-like en la inducción de la gliosis reactiva y la neuroinflamación luego de la isquemia cerebral - Rosciszewski, Gerardo Ariel (2018)
Stroke is the third leading cause of death in the world and is considered the leading cause of disability in adults. There are two types: ischemic and hemorrhagic, with the majority being ischemic.\nIn this thesis was studiedthe participation of Toll-like receptor (TLR) receptors in reactive gliosis and astroglial conversion to the proinflammatory phenotype that induces neurodegeneration. Using paradigms of gain and loss of function in vitro and in vivo we could establish that TLR4 increases its expression in glial cells (astrocytes and microglia) after induced cerebral ischemia in vivo in experimental models in rodents or after an exposure to deprivation of oxygen and glucose in vitro. Overexpression of TLR4 facilitates the conversion of astrocytes to the proinflammatory phenotype that induces neurodegeneration when TLR ligands are available, with NF-?B being the end effector of the pathway.\nOur experiments showed that both a PAMP such as LPS or a DAMP as the HMGB-1 molecule, released from cells in necrosis, act as activator of this signaling, although HMGB-1 shows ability to activate other molecular pattern receptors such as TLR2 and RAGE and shows some synaptogenic capacity on neurons in vitro. Finally, the in vivo application of a chemical inhibitor of NF-?B activation, sulfasalazine, modulates reactive gliosis, decreases neurodegeneration and alters the formation of the glial scar in animals subjected to experimental cerebral ischemia.\nBased on our results, we propose that TLR4 participates in the glial conversion to the proinflammatory-neurodegenerative phenotype by activating NF-?B. This cascade offers several control points that could be explored for the development of strategies to reduce neuroinflammation after cerebral ischemia.